Plate Loading Tests on Clay With Construction and Demolition Materials - Cabalar, Ali Fırat; İşbuğa, Volkan; Abdulnafaa, Mohammed Dafer; İşbuğa, Volkan (Springer Verlag, 2021)
This study presents a series results of plate loading tests on a clay with various construction and demolition (CD) materials conducted in a large-scale model box and a numerical verification on the use of these material mixtures. The tests have been applied to the clay with three different types of CD materials (concrete, asphalt, and brick) prepared in a reinforced concrete circular box with a diameter of 2.0 m and a depth of 1.5 m. The CD materials were added to the clay with a mix ratio of 10% by dry weight and then compacted at optimum water content (w(opt)) and corresponding maximum dry density (gamma(drymax)). The testing results have indicated that the CD materials increased the ultimate bearing capacity of the clay with a range of 50-75%. Furthermore, a remarkable correlation between the results of plate loading tests and numerical simulations made by a commercial finite element software (Plaxis 2D) was observed for all mixtures tested.
Keywords: Plate loading test; Clay; Construction and demolition materials; Finite element modelling